Contagion and evolution of the treatment of typhus in Peru in relation to the story of the tradition «El judío errante en el Cuzco» («The wandering Jew in Cuzco») - Espettia Salazar, Magui Luisa (2024)
This article will examine the presence of typhus in Peru based on the analysis of the story «El judío errante en el Cuzco» («The wandering Jew in Cuzco»), by the famous writer Ricardo Palma. In this work we are introduced to a foreign man of Semitic characteristics, who is accused of bringing the typhus epidemic to Peru by the inhabitants of Zurite, in Cuzco, who finally incinerate him in the town square, putting an end to the ravages of the disease at a national level. From this text, the magnitude of the impact that this bacterium had on the health of Peruvians in the 19th century and onwards, the ways in which this disease can be transmitted, its symptoms and the evolution of treatment up to the present day will be extracted. Finally, it will analyse how the lack of public health policies in remote areas of the country favours the proliferation of epidemic diseases such as typhus.